2013
DOI: 10.1088/2041-8205/764/2/l23
|View full text |Cite
|
Sign up to set email alerts
|

A DOUBLE-PEAKED OUTBURST OF A 0535+26 OBSERVED WITH INTEGRAL , RXTE , AND SUZAKU

Abstract: A normal outburst of the Be/X-ray binary system A0535+26 has taken place in August 2009. It is the fourth in a series of normal outbursts that have occured around the periastron passage of the source, but is unusual by starting at an earlier orbital phase and by presenting a peculiar double-peaked light curve. A first "flare" (lasting about 9 days from MJD 55043 on) reached a flux of 440 mCrab. The flux then decreased to less than 220 mCrab, and increased again reaching 440 mCrab around the periastron at MJD 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 37 publications
(48 reference statements)
9
36
0
Order By: Relevance
“…The observed decrease of the ratio implies an overall hardening of the spectrum with flux. A similar behavior is reported in Caballero et al (2013) for the normal double-peaked outburst of August 2009. The results of this analysis, i.e.…”
Section: Phase Averaged Spectrasupporting
confidence: 84%
“…The observed decrease of the ratio implies an overall hardening of the spectrum with flux. A similar behavior is reported in Caballero et al (2013) for the normal double-peaked outburst of August 2009. The results of this analysis, i.e.…”
Section: Phase Averaged Spectrasupporting
confidence: 84%
“…The mass and radius of the neutron star were assumed to be M = 1.5 M and R ns = 13 km, respectively , and the magnetic field was fixed to the value derived from the energy of the cyclotron line observed in 1A 0535+262. As discussed by Caballero et al (2013), the cyclotron line energy is observed at E ∼ 46 keV and does not change significantly with the luminosity. This implies that it most likely originates in the vicinity of the neutron star surface and, therefore, does provide an estimate of the magnetic field at the surface.…”
Section: Discussionmentioning
confidence: 66%
“…The magnetic field of the neutron star has been estimated to be B ∼ 5 × 10 12 G from the centroid energy of the so-called cyclotron resonance scattering feature (CRSF) observed at E cyc ∼ 45 keV in the X-ray spectrum of the pulsar. Unlike many other sources, 1A 0535+262 exhibits no significant variation of the line energy with luminosity, suggesting that the line is formed close to the surface of the neutron star (Caballero et al 2013).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…11 for the sources with known positive and negative correlations (shown by blue and red points, respectively). Finally, it is worth to note that for some transient pulsars no dependence of the cyclotron energy on luminosity has been detected for a wide range of luminosities (see, e.g., Caballero et al, 2013, for A 0535+26). Apart from the transient BeXBs, Reig and Roche (1999) pointed out the existence of persistent sources of the same Be/X type, but with low luminosities (10 34 − 10 35 erg s −1 ).…”
Section: Be Systems X-ray Pulsars and Properties Of Cyclotron Absorpmentioning
confidence: 99%